Multiproxy analysis of stabling layers in four middle bronze age byre-houses from the site of Oppeano 4D (Verona, Italy). - C Nicosia; M Dal Corso; S D'Aquino; M Baldan; M Bortolini; D Battistel; F Polisca (PLoS ONE)
Eight juxtaposed structures dating to the Middle Bronze Age (1650-1550 cal BCE) were exposed during rescue archaeological work in Oppeano (Veneto region, NE Italy). The site, named 'Oppeano 4D', was waterlogged and, as such, exhibited exceptional preservation of organic materials, including wooden structural remains and plant remains in the internal accretion deposits within each structure. In the present article, the internal stratifications of four such huts have been studied by means of a multi-disciplinary protocol including soil micromorphology and micro-XRF mapping, the study of botanical macro-remains, palynology, and the analysis of faecal biomarkers through GC-MS. Geoarchaeological and geochemical methods allowed to define deposit components necessary for the interpretation of the botanical records. The analyses revealed that the Oppeano structures are in fact byre-houses, where small herbivores were penned and in which other domestic activities, such as cereal processing by means of fire and food preparation, took place. Analyses also revealed that the floodplain offered several different natural environments for pastures and the collection of hay and litter for animal herding. These included the wetlands surrounding the site, the ruderal areas close to cultivated fields and settlement, and mixed deciduous mesophilous and hygrophilous woodlands. The carpological record showed a marked contrast among charred remains, pertaining to food processing, and uncharred seeds, fruits, buds, and twigs that derive from herbivore dung and fodder/bedding material. The palynological record reflects this dichotomy between activities related to human diet and animal penning that took place inside the structures and further revealed traces of natural environments used for pastures.